Storage Space Optimisation for Green Data Center - Nurul A., Emran; Abdullah, Noraswaliza (Elsevier, 2013)
The characteristic that determines a green data center is low amount of carbon footprint produced by its physical data storages. Increasing demand of data volumes in many data intensive applications call for additional physical data storages that are not only impractically large to maintain, but also contribute to the amount of carbon footprint produced. It is argued in this paper that, if storage space can be optimised to gain free spaces, the storage space requirement can be reduced. In this paper, a model to optimize database storage space by mining functional dependencies that are present among data sets is proposed. Sample data sets from the microbial domain have been used where data of large data volume raises storage space concern. The initial results of the implementation of the model that is necessary in designing a complete space optimization algorithm are presented.